PEMETAAN BATIMETRI UNTUK PERHITUNGAN VOLUME SEDIMENTASI DAN PENGERUKAN AREA KOLAM LABUH DERMAGA PLTU BARRU - Indra Mutiara; Herman Arruan (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
PLTU Barru is one of the generators that utilizes energy from coal to produce electrical energy, where the supply of coal to the generator location uses dock facilities where coal carrying ships carry out coal unloading activities. The dock capacity depends on the type of ship that will carry out unloading activities in the docking area. One of the problems that often occurs at this port is shallowing of the anchorage pond due to sediment deposition. This can cause obstruction of ships that will dock. Therefore, dredging is necessary. The aim of this research is to obtain water depth data in the anchorage pool area by carrying out a bathymetric map, then using this data the volume of sedimentation that occurs and the volume of dredging that may be carried out can be calculated. From the results of calculating the dredging volume using the cross section method with an elevation reference of -6 m LWS, the dredging volume is obtained at 165,851,923 m3